EFFECTS OF AGE AND SEASON ON SEMEN CHARACTERISTICS IN ARABIAN STALLIONS UNDER SUBTROPICAL CONDITIONS OF KUWAIT - Gamal Shawki; Tawfek Mohamed Barakat; Attia Mohamed Samy; Ahmed Alhamed AL-Mejren; Ayman Mesalam (Slovenian Veterinary Research, 2021)
Semen analysis is a valuable approach to assess stallion fertility. Many factors, including the age of the stallion and the season of year have been shown to influence semen quality. Therefore, the current study aimed to evaluate the influence of stallion’s age and season on the potential semen parameters and sperm morphology in Arabian stallions. A total of 108 ejaculates were collected using artificial vagina throughout the year from nine Arabian stallions aged 4-22 years, divided into three groups according to their ages; Group I (4-6 years), Group II (8-11years), and Group III (15-22 years). The ejaculates were analyzed immediately after collection for macroscopic and microscopic parameters using computer-assisted sperm analysis (CASA). Statistical analysis was applied to study the effect of the age of the stallion and season of semen collection on semen parameters. Our results showed a clear age-based differences (P < 0.05) with stallions aged from 4 to 11 years produce higher semen quality especially in sperm count, livability, motility and normal sperms compared with old stallions (15-22 years). Moreover, old stallions showed higher (P < 0.05) sperm abnormalities especially the secondary defects. The semen volume increased (P < 0.05) in the spring, and sperm concentration was higher (P < 0.05) in the winter and autumn, while, no significant variation in total sperm number between different seasons. Moreover, the livability, motility, normal sperms and progressive sperm motility were higher (P < 0.05) in hot season (breeding season) compared with cold season, but abnormal sperms were lower. These data suggest that, older stallions (15-22 years) produce ejaculates of larger volume but the motility, viability, and abnormalities percent were better in ejaculates collected from stallions aged 4-11 years. Ejaculates collected during spring and summer showed better characteristic than that collected during autumn and winter.